Kekuatan Kinerja Pemasaran Dan Sosial Media Dalam Meningkatkan Keunggulan Bersaing - Deya Mentari Octavia Anugerah; R Deni Muhammad Danial; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Competitive advantage becomes an important thing for companies, companies must be able to analyze what are the company's advantages in order to compete with competitors. The purpose of this study is to determine the effect of marketing and social media performance on competitive advantage. This study uses quantitative methods. The population in this study were Scarlett Whitening users in the city of Sukabumi and the sample used was 100 respondents. The data analysis technique used is multiple linear regression analysis and the sample technique used is probability sampling. The results of this study indicate that simultaneously and partially the performance of marketing and social media has a significant and positive influence on competitive advantage. The results of the f test, namely the Fcount value of 62.417> 3.08, show that Fcount is greater than Ftable and the correlation results in this study have a strong and high value of 0.565. While the value of the results of the t-test, namely Tcount 3.327 > 1.983 shows that the value of Tcount is greater than Ttable so that it can be concluded that marketing and social media performance variables have an influence on competitive advantage. Keyword : Strength of Marketing, Social Media, Competitive Advantage